2020
DOI: 10.1007/s00404-020-05697-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing placental stiffness using ultrasound shear-wave elastography in healthy and preeclamptic pregnancies

Abstract: Purpose-To measure the stiffness of the placenta in healthy and preeclamptic patients in the second and third trimesters of pregnancy using ultrasound shear-wave elastography (SWE). We also aimed to evaluate the effect of age, gestational age, gravidity, parity and body mass index (BMI) on placental stiffness and a possible correlation of stiffness with perinatal outcomes.Methods-In a case-control study, we recruited a total of 47 singleton pregnancies in the second and third trimesters of which 24 were health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…In a recent study, Spiliopoulos et al (27) found that the mean placental stiffness was significantly higher in preeclamptic pregnancies compared to controls in the third trimester. In particular, the SWE technique seems useful in clinical practice for investigating the associations between placental stiffness and adverse pregnancy outcomes in highrisk pregnancies.…”
Section: Discussionmentioning
confidence: 93%
“…In a recent study, Spiliopoulos et al (27) found that the mean placental stiffness was significantly higher in preeclamptic pregnancies compared to controls in the third trimester. In particular, the SWE technique seems useful in clinical practice for investigating the associations between placental stiffness and adverse pregnancy outcomes in highrisk pregnancies.…”
Section: Discussionmentioning
confidence: 93%
“…It showed that the elastic modulus of the perineal body, the SWE of the anterior lip and the SWE of the posterior lip were significantly changed for primipara after pregnancy and delivery. The results of Spiliopoulos et al pointed out that the average Young's modulus of the perineum in the non-fertile group was greater than that of the cesarean section, and the average Young's modulus of the perineum in the cesarean section was greater than that of the vaginal delivery group (P<0.05), suggesting that the damage of the perineal body is more obvious in the vaginal delivery group (47). In cesarean section, due to the influence of pregnancy uterus weight and hormone levels, the muscle strength of the perineal body is impaired and the elasticity value is reduced (48).…”
Section: Discussionmentioning
confidence: 98%
“…Impairment of perfusion in tissues results in hypoxia, and collagen and fibrin deposition increases in the environment. These situation lead to fibrosis and tissue stiffness increases [ 22 ]. In the presence of gestational hypertension and/or intrauterine growth retardation, pathological findings showing infarction, ischemic changes, and fibrosis are frequently detected in the placenta [ [23] , [24] , [25] ].…”
Section: Discussionmentioning
confidence: 99%